Odor Sensitivity After Intranasal Insulin Application Is Modulated by Gender - Rodriguez-Raecke, Rea; Brünner, Yvonne F.; Kofoet, Anja; Mutic, Smiljana; Benedict, Christian; Freiherr, Jessica (Frontiers in Endocrinology, 2018)
With this experiment, we aimed to explore the influence of intranasal insulin on olfactory sensitivity for the odors n-butanol and peanut in a placebo-controlled, double-blind setting in a within-subject design. All subjects participated in two experimental sessions on separate days and received either intranasal insulin or placebo in a pseudorandomized order. Application was followed by two olfactory threshold tests for n-butanol and peanut in a pseudorandomized order. After a single dose of intranasal insulin (40 IU) or placebo (0.4 ml), olfactory sensitivity for the odorants n-butanol and peanut were examined in 30 healthy normosmic participants (14 females). Measured blood parameters revealed no decrease in plasma glucose, however, insulin, leptin and cortisol levels were affected following intranasal application. Females’ but not males’ olfactory sensitivity for n-butanol was lower after intranasal insulin administration vs. placebo. In contrast, olfactory sensitivity for peanut was not influenced by intranasal insulin application. Our results indicate that the effects of cortical insulin levels on processing of specific odors is likely modulated by gender, as central increase of insulin concentration led to a reduced olfactory sensitivity for n-butanol in females only.